ELECTROPHYSIOLOGICAL ASSESSMENT OF AUTONOMIC NERVOUS SYSTEM ADAPTATION TO HEAT STRESS IN YOUNG ADULTS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Adaptation of the autonomic nervous system plays a crucial role in maintaining physiological stability under environmental stress conditions. In regions characterized by high ambient temperatures, heat stress represents a significant challenge to autonomic regulation, particularly in young adults. At early stages, adaptive disturbances may remain clinically silent while functional regulatory changes are already present. This study examines autonomic nervous system adaptation to heat stress in young adults using an electrophysiological and biophysical approach. Cardiac rhythm dynamics were analyzed to evaluate autonomic balance and regulatory flexibility under resting conditions associated with thermal exposure. Emphasis was placed on functional signal behavior rather than clinical symptomatology. The analysis revealed electrophysiological patterns indicative of reduced adaptive capacity, suggesting early autonomic strain in response to heat stress. The findings indicate that electrophysiological assessment provides sensitive markers of autonomic adaptation to environmental heat. Biophysical interpretation of autonomic regulation may support early identification of functional vulnerability and contribute to preventive strategies in populations exposed to prolonged thermal stress.